Analisis Pengelolaan Aset Daerah Pada Pemerintah Daerah Kabupaten Bandung Barat - Ilham Fadilah; Rahma Nazila Muhammad; Rendra Trisyanto Surya (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to determine the process of regional asset administration, asset administration problems, the impact of fixed asset problems, problem solving steps, and efforts to improve regional asset management. Type of research is descriptive qualitative with interviews as the main tool to collect data with resource persons from the Head of the Assets Division, the Head of the Asset Administration Sub-Sector, the Head of the Asset Security Sub-Section and the Property Manager. The results showed that the West Bandung Regency Government carried out the regional asset administration process in accordance with applicable regulations, although they still encountered problems with land assets, equipment and machinery, as well as buildings and buildings caused by the delegation of assets from Bandung Regency, resource competence was not maximized, insufficient budget and the census of goods has not been carried out. The West Bandung Regency Government has resolved existing problems by improving data on the system, land certification, controlling current assets, field observations, routine consolidation, updating information systems, increasing human resource competence, census of goods and commitment of the leaders. The results obtained from this study are to increase knowledge and understanding of the sources of regional asset management problems in general. The author suggests for further research to discuss the relationship between BPK's opinion and the results of regional asset management.